Magnetic Field Structure and Activity of the He-burning Giant 37 Comae. Issue Volume 9:Issue S302(2013) (7th August 2014) - Tsvetkova, S.; Petit, P.; Konstantinova-Antova, R.; Aurière, M.; Wade, G. A.; Charbonnel, C.; Drake, N. A.
Abstract: We present the first magnetic map of the late-type giant 37 Com. The Least Squares Deconvolution (LSD) method and Zeeman Doppler Imaging (ZDI) inversion technique were applied. The chromospheric activity indicators Hα, S-index, Caii IRT and the radial velocity were also measured. The evolutionary status of the star has been studied on the basis of state-of-the-art stellar evolutionary models and chemical abundance analysis. 37 Com appears to be in the core Helium-burning phase.